DEVITALIZED VASCULAR PROSTHESES: IN VIVO STUDY - D. V. Byzov; N. A. Chizh; I. P. Mikhaylova; Ye. N. Pushkova; O. P. Synchykova; B. P. Sandomirsky (Вестник трансплантологии и искусственных органов)
Porcine intrathoracic arteries were devitalized by application of low temperatures and electron beam irradiati- on. The resulted connective tissues vascular scaffolds could be used as the prosthesis of small diameter arteries (≤6 mm). Biocompatibility, immunogenicity degree and thrombogenicity were estimated in the study. Results of electron microscopy are presented. Described treatment reduces an immunogenicity of xenoarteries, their ade- quate functioning during 6 months was shown by means of experimental surgeries.